Strength and Weakness Characteristics of Using Polymer Based Alternative to Steel Mesh In Underground Coal Mine Strata - Akash Talapatra (JACEE (Journal of Advanced Civil and Environmental Engineering), 2019)
Nowadays a viable development of polymer based material as an alternative to the steel mesh material has been increased at a notable amount for providing enough support in the underground roadways. This feasibility study done on the development of using polymer based alternative is related with both of the chemical & physical properties of the selected material. If the polymer alternative has a considerable amount of capability to tolerate all the physical & material constraints equal to or above the normal steel mesh, then the possibility of using polymeric alternatives have been increased at a greater extent. For this reinforcement test, an experiment practice would be done by comparing the mechanical properties of the steel mesh with the polymeric material such as modulus property, elongation-at-break, yield stress etc. After that, a suitable polymer based alternative will be applied for underground roadway support in upcoming days.